Mechanical, thermal and processing properties of oil palm empty fruit bunch-filled impact modified unplasticised poly (vinyl chloride) composites - Abu Bakar, Aznizam (2006)
The main objective of this study is to investigate the effects of EFB filler and two types of impact modifiers on mechanical and thermal properties, and processability of PVC-U composites. Two methods were used to prepare the samples, i.e., compression moulding and single screw extrusion. A torque rheometer was used to determine the fusion characteristics of PVC. EFB increased the flexural modulus of 22 % but decreased the impact strength and flexural strength of 20 % and 18 % of PVC, respectively, as the filler contents increased. Increasing the impact modifiers contents, on the other hand, improved the impact strength but slightly decreased the flexural modulus and flexural strength. Acrylic impact modifier performed better than CPE in producing composites with balanced properties of toughness and stiffness. The use of Prosil 9234 coupling agent for filler surface treatment proved to be more reliable compared to NZ 44 in providing better filler-matrix interaction. The TGA study showed that both the EFB filler and acrylic impact modifier decreased the PVC thermal stability. Oil residues in the EFB did not influence the mechanical properties of PVC-U composites. The fusion time also decreased significantly with the addition of acrylic. Both the temperature and screw speed significantly influenced the fusion level of PVC, hence the mechanical properties of the extrudates. Overall, the study showed that EFB has the potential to be used as filler for PVC-U composites